Ефективність мультифокальної інтраокулярної корекції пресбіопії після факоемульсифікації катаракти - Завгородня, Наталія Григорівна; Безденежна, Ольга Олександрівна; Костровська, Катерина Олегівна; Безденежний, С. В.; Казанський, А. В.; Zavgorodnya, N. G.; Bezdenezhna, O. O.; Kostrovska, K. O.; Bezdenezhnyi, S. V.; Kazanskyi, A. V. (My University, 2021)
Мета: оцінити якість зору і задоволеність пацієнтів після факоемульсифікації катаракти при імплантації різних видів мультифокальних ІОЛ. Multifocal intraocular lens implantation has become increasingly popular in view of improvements in optics. The results of phacoemulsification in 40 patients (19 males and 21 females, 76 eyes) were retrospectively analyzed. Uncorrected distance visual acuity was 1.0 in all the patients; target refraction was achieved in 100% of the cases. One hundred per cent of patients with AT LISA 839 MR Tri managed without eyeglasses at various distances. Multifocal intraocular lenses implantation is a high-performance, safe, predicted and stabile technique for presbyopia, which eliminates the need for patients to use eyeglasses in everyday life.
Efficacy of multifocal lenses for presbyopia following phacoemulsification